Research on Plant Genomics and Breeding (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent decades, crop breeding has greatly benefited from the knowledge of plant genomics and genetics, as well as the development of modern biotechnologies. Exploring the genetic basis and molecular mechanisms underlying various plant developmental and growth processes is imperative, as they underpin crop yield, grain quality, and stress adaptations. The goal of this Special Issue in IJMS, “Research on Plant Genomics and Breeding”, is to present an overview of the latest fundamental discoveries in the field of plant genomics, as well as the potential utilization of biotechnologies in crop genetic improvement. We welcome all readers to this Reprint that covers several fields: the genetic and functional characterization of genes regulating important plant development processes or agronomic traits; the genetic improvement in crops using gene editing and other modern biotechnologies; and the discovery, characterization, and application of germplasm resources with elite traits.